Extended and treatment-oriented classification of parotid duct stenosis - Koch, Michael; Iro, Heinrich (Laryngoscope, 2017)
OBJECTIVES/HYPOTHESIS: To provide an extended and treatment-oriented classification of parotid duct stenosis that might be useful in the management of this condition. STUDY DESIGN: Retrospective study in a tertiary referral center. METHODS: A total of 550 symptomatic stenoses of the parotid gland excretory duct in 445 patients were analyzed. Sialendoscopy was performed with semirigid endoscopes. The tissue quality, location, grade of luminal narrowing, and length and number of the stenoses were assessed. RESULTS: Inflammation-dominant stenosis (type 1) was found in 8.9% of the patients, web-associated fibrous stenosis (type 2) in 19.5%, and fibrous (type 3) in 71.6%. Multiple stenoses (≥3) were found in 2.8% of patients, and bilateral stenoses in 11.9%. Type 1 stenoses differed significantly from type 3 stenoses, with lower grades. Type 3 stenoses showed significantly higher grades of luminal narrowing than the other two types (P = .0001). Type 2 stenoses were significantly shorter in comparison with the other two types (P = .0001). Multiple stenoses were observed significantly more often in type 2 than in type 3 stenoses (P = .0001). Due to these differences, the type of stenosis appears to be the most important criterion in the treatment-oriented classification. CONCLUSIONS: Significant differences between the different stenoses were observed. Type 1 stenosis may be considered as a precursor of type 3 stenosis, but type 2 stenosis showed significantly different characteristics. The differences prescribed in this classification may be helpful in the management of parotid duct stenoses. LEVEL OF EVIDENCE: 4. Laryngoscope, 2016 127:366-371, 2017.
EVALuna2:33184